Patterns of practice in palliative radiotherapy for bleeding tumours in the Netherlands; a survey study among radiation oncologists. (February 2019) - Strijbos, Jennifer; van der Linden, Yvette M.; Vos-Westerman, Hanneke; van Baardwijk, Angela; ,
Highlights: Current practice in the Netherlands for radiotherapy of bleeding tumours varied considerably. Most often a single fraction of radiotherapy is chosen to treat a bleeding tumour. The choice of radiotherapy schedule is mainly influenced by patient related factors. Abstract: Background and purpose: Palliative radiotherapy (RT) is one of the treatment options for bleeding tumours; a frequent symptom in patients with advanced cancer. The optimal RT schedule is however unclear. This study explores the current pattern of practice of palliative RT for bleeding tumours in the Netherlands. Materials and methods: An internet-based questionnaire, including respondent characteristics, factors influencing the choice of RT schedules and five patient case scenarios, was sent to all members of the Dutch Society for Radiation Oncology. Descriptive statistics were used to evaluate the results. Results: The response rate was 125/374 (34%); representing 20 out of 21 Dutch RT departments. Most reported influencing factors were performance status, prognosis, patients' comfort and patients' choice. Most preferred RT schedules were 1 × 8 Gy for hematemesis, 1 × 8 Gy and 5 × 4 Gy for haemoptysis, 5 × 4 Gy for haematuria, 5 × 5 Gy for rectal bleeding, 1 × 8 Gy, 5 × 4 Gy and 10-13 × 3 Gy for vaginal bleeding. Conclusions: The current patterns of practice in the Netherlands for bleeding tumours varied considerably. Most often a single fraction is chosen (35% of all cases), followed by a five-fraction schedule (30% of all cases). The choice of an RT schedule is mainly influenced by patient related factors.